PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP KINERJA SKPD DINAS PERTAMBANGAN DAN ENERGI ACEH - Nurhayati Nurhayati (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2014)
The purpose of this research is to know the impact of participation in budget arranging and goal budget clarity to the performance of SKPD Mining and Energy Department of Aceh.The samples of this research are the employees that were involved in the budget arranging and the budget user of SKPD in the Mining and Energy Department of Aceh. There were 45 respondents in total. The choosing of the samples was done by using the simple random sampling method. The analytic method that was used in this research is the multiple linier regression method.The result of this research shows (1) variably participation in budget arranging and goal budget clarity affects the performance of the SKPD in the Mining and Energy Department of Aceh, (2) Partially participation in budget arranging affects significantly on the performance of the SKPD while the goal budget clarity affects the performance of the SKPD in the Mining and Energy Department of Aceh